Sensory Processing as a Predictor of Leisure Participation in Early Adolescents - Young-Eun Choi; Hyerim Jung (MDPI AG, 2021)
Sensory processing may be associated with adolescents' preferences for different leisure activities. However, knowledge about how different sensory processing patterns may relate to adolescents' participation in leisure activities is scarce. This study sought to investigate the relationship between sensory processing and leisure participation in early adolescents. Study participants were typical early adolescents aged from 11 to 12 years (mean = 11.88 ± 0.33, n = 140). The Adolescent/Adult Sensory Profile (AASP) and Children's Assessment for Participation and Enjoyment (CAPE) were used to determine the participants' sensory processing abilities. Correlational and multiple regression methods were employed to analyze the relationship between sensory processing and leisure participation. There were significant positive relationships between sensory seeking and participation (r = 0.177-0.350, p = 0.000-0.037). There were also significant negative relationships between low registration, sensory sensitivity, and overall participation (r = −0.202, p = 0.017, r = −0.212, p = 0.012). We found that formal activities, skill-based activities, and self-improvement activities were the main distinguishing factors between sensory processing types. Results suggest that sensation seeking and sensory sensitivity from the AASP were predictive of leisure participation. This study provides evidence to inform practices regarding the association of sensory processing and leisure participation and supports the need for assessing sensory processing in early adolescents.